Restore the name Lilium tenii H.Lév. (Liliaceae), which has priority over the later synonym L. lijiangense L.J.Peng - Gao, Yun-Dong; Gao, Xin-Fen (Phytotaxa, 2020)
The name Lilium tenii H.Léveillé (1909: 263) was assigned by Hector Léveillé to a specimen collected by Father Siméon Ten on 15 August 1907 from Dongchuan (Tong-Tchouan) of Yunnan Province, China. The name L. tenii has long been treated as a synonym for Lilium primulinum var. ochraceum (Franch.) Stearn (1948: 13). The treatment was based on the monograph of Chinese lilies by William Wright Smith (1923). Smith (1923) mentioned Lilium tenii when he revised L. ochraceum Franchet (1892: 319), which was later reduced to a variety under L. primulinum Baker (1892: tab. 7227). However, Smith (1923) did not treat L. tenii as a synonym of L. ochraceum. Instead, Smith (1923) pointed the distinctness of L. tenii by saying: ‘This is a puzzling plant….. I can find nothing quite like the leaves of Tenii……some of the leaves having 9–11 distinct nerves. On the evidence before me I cannot justify the reduction of this species, at any rate meanwhile, to any previously described species. It is a near ally of ochraceum (p134–135)’. As part of his revision of the taxonomy of Léveillé, Smith (1923) regarded L. tenii as ‘possibly valid (p141)’ and did not synonymize it within any other species.